THE REFERENCE MODEL OF CONTROL INSTITUTION AGENT: EXPERIENCE PRODUCT OF INTOSAI - Khmelkov, Adriy (Social Economics, 2020)
The article gives a research to establish the mental representations of the reference model agent of the Institute of Control Supreme Audit Institution (SAI) through the prism of supranational concentrated experience of the International organization of Financial Control supreme bodies in the System of professional documentation (IFPP). The proposals concerning changes in the direction of extension, the perception of experience not only as INTOSAI professional standards to hone their algorithms of control measures, but also as a set of principles, values, standards and requirements by which it is possible to construct the Institute of control agent at the abstract level and to build a Supreme audit institution in practice are developed.  Recently, INTOSAI has carried out a new structuring of experience in implementing state financial control and grouped it in professional System documentation (IFPP). The new logic of supranational experiences of INTOSAI allowed to describe the author's vision in the article on a proper basis. The results of the study became a reference model  of an Institute of control agent as a financial control body, which is formed on an appropriate form, and filled with a relevant content. This fully reflects the global expertise and ideas of the professional community on the issues of control over public resources. The study gave a positive answer to the question about the possibility of the perceptual experience of INTOSAI for the construction of the model agent of the Institute of control. The scientific results in the form of a reference model of an Institute of control agent , is not only of a theoretical nature as a subject field in the Institute of control sphere, which can be used in studies of institutional design but has an applied nature, through further development of the methodological apparatus for institutional theories of comparative analysis: in case of new subjects of the state financial control creation (i.e. SAI) or in case of need to collate and compare the higher control authorities that are already operating with a reference model, among all member countries of INTOSAI, on the subject of the diagnosis of any deviations from the standard.